Agile Leadership and Career Succes: a Culture of “AKHLAK” as Complementary Partial Mediation - Srimulyani, Veronika Agustini; Anatasya, Vira Gupti (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
Agile leadership is becoming more relevant in today’s fast-changing world. Leaders who embrace this approach foster teamwork, adapt quickly to change, and create an environment where employees can thrive. This study explores how agile leadership directly enhances career success and how it does so indirectly through the “AKHLAK” culture. The research was conducted with 50 permanent employees from PT INKA (Persero) in the General Department and HR Division. Data was collected through questionnaires and analyzed using SEM-PLS. The findings show that agile leadership significantly strengthens the “AKHLAK” culture and improves career success. Additionally, the “AKHLAK” culture itself plays a crucial role in boosting career growth and acts as a bridge between agile leadership and success. By encouraging collaboration, innovation, and adaptability, agile leadership helps embed “AKHLAK” values within employees, ultimately leading to greater achievements. In an era of rapid change, businesses must stay flexible and responsive. To remain competitive and relevant, organizations need leaders who embrace agility and inspire their teams to grow.